Determination of liver‐specific r2* of a highly monodisperse USPIO by 59Fe iron core‐labeling in mice at 3 T MRI. (30th July 2014) - Raabe, Nina; Forberich, Evelyn; Freund, Barbara; Bruns, Oliver T.; Heine, Markus; Kaul, Michael G.; Tromsdorf, Ulrich; Herich, Lena; Nielsen, Peter; Reimer, Rudolph; Hohenberg, Heinrich; Weller, Horst; et al.
<x xml:space="preserve">Abstract</x> Accurate determination of tissue concentration of ultrasmall superparamagnetic iron oxide nanoparticles (USPIO) using T2* MR relaxometry is still challenging. We present a reliable quantification method for local USPIO amount with the estimation of the liver specific relaxivity r2* using monodisperse 59Fe‐core‐labeled USPIO (59FeUSPIO). Dynamic and relaxometric in vivo characteristics of unlabeled monodisperse USPIO were determined in MRI at 3 T. The in vivo MR studies were performed for liver tissue with 59FeUSPIO using iron dosages of 9 (n = 3), 18 (n = 2) and 27 (n = 3) µmol Fe kg−1 body weight. The R2* of the liver before and after USPIO injection (∆R2*) was measured and correlated with 59Fe activity measurements of excised organs by a whole body radioactivity counter (HAMCO) to define the dependency of ∆R2* and 59FeUSPIO liver concentration and calculate the r2* of 59FeUSPIO for the liver. Ultrastructural analysis of liver uptake was performed by histology and transmission electron microscopy. ∆R2* of the liver revealed a dosage‐dependent accumulation of 59FeUSPIO with a percentage uptake of 70–88% of the injection dose. Hepatic ∆R2* showed a dose‐dependent linear correlation to 59FeUSPIO activity measurements (r = 0.92) and an r2* in the liver of 481 ± 74.9 mm−1 s−1 in comparison to an in vitro r2* of 60.5 ± 3.3 mm−1 s−1. Our results indicate that core‐labeled 59FeUSPIO can be used to quantify the local amount of USPIO and to estimate the liver‐specific relaxivity r2*. Copyright © 2014 John Wiley & Sons, Ltd.